Directing the mechanism of CO2 reduction by a Mn catalyst through surface immobilization. Issue 10 (26th February 2018) - Walsh, James J.; Forster, Mark; Smith, Charlotte L.; Neri, Gaia; Potter, Richard J.; Cowan, Alexander J.
Abstract : Immobilization of a Mn polypyridyl CO2 reduction electrocatalyst on nanocrystalline TiO2 electrodes yields an active heterogeneous system and also significantly triggers a change in voltammetric and catalytic behaviour, relative to in solution. Abstract : Immobilization of a Mn polypyridyl CO2 reduction electrocatalyst on nanocrystalline TiO2 electrodes yields an active heterogeneous system and also significantly triggers a change in voltammetric and catalytic behaviour, relative to in solution. A combination of spectroelectrochemical techniques are presented here to elucidate the mechanism of the immobilized catalyst in situ .